2018
DOI: 10.1073/pnas.1713501115
|View full text |Cite
|
Sign up to set email alerts
|

Ants avoid superinfections by performing risk-adjusted sanitary care

Abstract: Being cared for when sick is a benefit of sociality that can reduce disease and improve survival of group members. However, individuals providing care risk contracting infectious diseases themselves. If they contract a low pathogen dose, they may develop low-level infections that do not cause disease but still affect host immunity by either decreasing or increasing the host's vulnerability to subsequent infections. Caring for contagious individuals can thus significantly alter the future disease susceptibility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 60 publications
2
46
0
Order By: Relevance
“…However, they had a higher proportion of ant-microbial symbionts than surrounding bare soils including Aspergillus pseudonomius, Aspergillus NRRL-32683, Mucor circinelloides, and Cryptococcus laurentii, which are involved in the production of antibiotics [14]. These findings are in agreement with recent research [15], and suggest that ant nests maintain a hygienic environment in their nests.…”
supporting
confidence: 89%
“…However, they had a higher proportion of ant-microbial symbionts than surrounding bare soils including Aspergillus pseudonomius, Aspergillus NRRL-32683, Mucor circinelloides, and Cryptococcus laurentii, which are involved in the production of antibiotics [14]. These findings are in agreement with recent research [15], and suggest that ant nests maintain a hygienic environment in their nests.…”
supporting
confidence: 89%
“…During infection, M. brunneum can suppress the host immune system with secondary metabolites [ 42 ] and physically break host cells and tissues with its invading hyphae, which may allow B. floridanus to proliferate and escape bacteriocytes. This would require the host to elicit a multifaceted immune response involving both antifungal and antibacterial pathways of the innate immune system, analogous to a super-infection in insects where two distinct pathogens infect the host, hastening and increasing mortality [ 72 , 73 , 74 , 75 ]. Escaped B. floridanus in the haemocoel could thereby give the invading M. brunneum the upper hand in the battle against the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant study conducted in the ant Lasius neglectus, however, Konrad et al [35] demonstrated that allogrooming provides direct benefits to both recipients and donors, as it allows donors to prime their own immune system and thus boost their defences against future pathogen exposure. Interestingly, a follow-up study recently showed that these direct benefits are pathogen-specific in that workers immune-primed with one type of pathogen preferentially direct their future allogrooming behaviours toward individuals infected with the same compared to a different pathogen [36].…”
Section: On the Importance Of Reproductive Division Of Labourmentioning
confidence: 99%